2023
DOI: 10.3389/fmars.2023.1129057
|View full text |Cite
|
Sign up to set email alerts
|

Marine invertebrates and noise

Abstract: Within the set of risk factors that compromise the conservation of marine biodiversity, one of the least understood concerns is the noise produced by human operations at sea and from land. Many aspects of how noise and other forms of energy may impact the natural balance of the oceans are still unstudied. Substantial attention has been devoted in the last decades to determine the sensitivity to noise of marine mammals—especially cetaceans and pinnipeds—and fish because they are known to possess hearing organs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 229 publications
0
45
0
Order By: Relevance
“…Recently, there has been a shift in focus to studying the impact of anthropogenic noise on marine life (Jerem & Mathews, 2021; Kunc & Schmidt, 2019; Mickle & Higgs, 2018). Studies on underwater noise and marine invertebrate systems are few (as opposed to marine mammals), but particle motion in the sediment and water rather than sound pressure is detrimental (Solé et al., 2023). We included additional stressors from our literature searches – noise from acoustic stimuli such as seismic air guns and exposure to electromagnetic fields from buried cables (Celi et al., 2013; Celi et al., 2015; Filiciotto et al., 2014, 2016; Filiciotto et al., 2018; Fitzgibbon et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a shift in focus to studying the impact of anthropogenic noise on marine life (Jerem & Mathews, 2021; Kunc & Schmidt, 2019; Mickle & Higgs, 2018). Studies on underwater noise and marine invertebrate systems are few (as opposed to marine mammals), but particle motion in the sediment and water rather than sound pressure is detrimental (Solé et al., 2023). We included additional stressors from our literature searches – noise from acoustic stimuli such as seismic air guns and exposure to electromagnetic fields from buried cables (Celi et al., 2013; Celi et al., 2015; Filiciotto et al., 2014, 2016; Filiciotto et al., 2018; Fitzgibbon et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a shift in focus to studying the impact of anthropogenic noise on marine life (Jerem & Mathews, 2021;Kunc & Schmidt, 2019;Mickle & Higgs, 2018). Studies on underwater noise and marine invertebrate systems are few (as opposed to marine mammals), but particle motion in the sediment and water rather than sound pressure is detrimental (Solé et al, 2023).…”
Section: Crustacean Welfare and Sources Of Stressmentioning
confidence: 99%
“…Consequently, motorboat noise should affect the fitness of D. magna . Absence to negative effects are expected according to various chronic and acute exposure experiments on invertebrates (Solé et al, 2023), but note that a positive effect was found for D. magna chronically exposed to broadband noise (Prosnier, Rojas, Valéro, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of noise on large invertebrates, such as decapods or bivalves, have recently received substantial interest (see the reviews of Popper et al (2001) and Solé et al (2023)), research largely neglected zooplanktonic invertebrates (Hawkins et al, 2015; Prosnier, 2022; Vereide & Kühn, 2023), despite their ecological importance and general use as bioindicators in ecotoxicology (Parmar et al, 2016). Although zooplankton do not possess hearing structures, they present mechanoreceptors that allow them to detect particle motion, the other component of a sound with pressure (Gassie et al, 1993; Buskey et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite representing >90% of marine organisms, there is a lack of information regarding the effects of sound on invertebrates (Nedelec et al, 2014). Further studies are thus urgently required to better understand the impact of noise pollution on these marine organisms (Sole ́et al, 2023). Among invertebrates, bivalves are some of the most commercially and ecologically valuable.…”
Section: Introductionmentioning
confidence: 99%